Affinity Maturation Drives Epitope Spreading and Generation of Proinflammatory Anti–Citrullinated Protein Antibodies in Rheumatoid Arthritis - Elliott, Serra E.; Kongpachith, Sarah; Lingampalli, Nithya; Adamska, Julia Z.; Cannon, Bryan J.; Mao, Rong; Blum, Lisa K.; Robinson, William H. (Arthritis & rheumatology (Hoboken, N.J.), 2018)
Objective Rheumatoid arthritis (RA) is characterized by the presence of anti–citrullinated protein antibodies (ACPAs); nevertheless, the origin, specificity, and functional properties of ACPAs remain poorly understood. The aim of this study was to characterize the evolution of ACPAs by sequencing the plasmablast antibody repertoire at serial time points in patients with established RA. Methods Blood samples were obtained at up to 4 serial time points from 8 individuals with established RA who were positive for ACPAs by the anti–cyclic citrullinated peptide test. CD19+CD3−IgD−CD14−CD20−CD27+CD38++ plasmablasts were isolated by single‐cell sorting and costained with citrullinated peptide tetramers to identify ACPA‐expressing plasmablasts. Cell‐specific oligonucleotide barcodes were utilized, followed by large‐scale sequencing and bioinformatics analysis, to obtain error‐corrected, paired heavy‐ and light‐chain antibody gene sequences for each B cell. Results Bioinformatics analysis revealed 170 persistent plasmablast lineages in the RA blood, of which 19% included multiple isotypes. Among IgG‐ and IgA‐expressing plasmablasts, significantly more IgA‐expressing than IgG‐expressing persistent lineages were observed (P < 0.01). Shared complementarity‐determining region 3 sequence motifs were identified across subjects. A subset of the plasmablast lineages included members derived from later time points with divergent somatic hypermutations that encoded antibodies that bind an expanded set of citrullinated antigens. Furthermore, these recombinant, differentially mutated plasmablast antibodies formed immune complexes that stimulated higher macrophage production of tumor necrosis factor (TNF) compared to antibodies representing earlier time point–derived lineage members that were less mutated. Conclusion These findings demonstrate that established RA is characterized by a persistent IgA ACPA response that exhibits ongoing affinity maturation. This observation suggests the presence of a persistent mucosal antigen that continually promotes the production of IgA plasmablasts and their affinity maturation and epitope spreading, thus leading to the generation of ACPAs that bind additional citrullinated antigens and more potently stimulate macrophage production of TNF.